Vittorini and the problem of evil - Moloney, Brian (Spunti e Ricerche, 2016)
Vittorini's Uomini e no had relatively little success in post-war Italy, one possible factor being the author's refusal to idealize his partisans. It is a more complex novel than its critics allow. Vittorini has not merely been brought to face with the inadequacy of his earlier formulation of the problem of evil: we need no prophet to tell us that we are an amalgam of good and bad. His achievement lies, rather, in his ability, by means of allegory and symbol, to analyse the events of his time and to reveal the social and psychological mechanisms which enable evil to flourish.